Bacteriological Profile and Antibiotic Susceptibility Patterns in Lower Respiratory Tract Infection at a Tertiary Care Teaching Hospital - Jitendra Singh; Arpita Shah; Hemali Parmar; Bithika Duttaroy (GAIMS Journal of Medical Sciences)
Aim: To study the bacterial profile, along with antibiotic susceptibility pattern of isolates from suspected cases of LRTIs attending the tertiary care study area.